The links between health-related behaviors and life satisfaction in elderly individuals who prefer institutional living - AY, SERAP (BMC, 2007)
Background: Life satisfaction among residents of institutions is becoming an important issue in a rapidly aging population. The aim of this cross-sectional study was to investigate the links between life satisfaction and health-related behaviors amongst functionally independent elderly people who prefer institutional living in Istanbul, Turkey. Methods: The socio-demographic characteristics, health-related behaviors, leisure-time activities and fall histories of 133 residents of an institution in Istanbul were assessed by a structured questionnaire during face-to-face interviews. A validated life-satisfaction index questionnaire (LSIA) was completed. Results: The mean age of the study group was 73.9 +/- 8.0 ( range 60 - 90 years). Within the group, 22.6% had never married and 14.3% had university degrees. The majority (71.4%) were in the low income bracket. The overall mean LSI-A score was 20.3 +/- 5.9. Participants who declared moderate/ high income levels had a significantly higher mean LSI-A score than those in the low-income bracket ( p = 0.009). Multivariate analysis of the data suggested that leisure-time activities and participation in regular physical activities are significant predictors of LSI-A scores (R-2: 0.112; p = 0.005 and p = 0.02, respectively). Conclusion: The findings imply that regular physical activity and leisure-time activities are significantly related to life satisfaction among residents in institutions. Participation in physical activity and leisure-time activity programs may help to improve the life satisfaction of elderly people living in institutions.
Keywords: QUALITY-OF-LIFE; PHYSICAL-ACTIVITY; OLDER PERSONS; RISK-FACTORS; COMMUNITY; PEOPLE; POPULATION; IMPAIRMENT; PREDICTORS; SURVIVAL